2015
DOI: 10.1016/j.cja.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of unconventional aerodynamic characteristics of an elliptic airfoil

Abstract: The aerodynamic characteristics of elliptic airfoil are quite different from the case of conventional airfoil for Reynolds number varying from about 10 4 to 10 6 . In order to reveal the fundamental mechanism, the unsteady flow around a stationary two-dimensional elliptic airfoil with 16% relative thickness has been simulated using unsteady Reynolds-averaged Navier-Stokes equations and the c À Re ht transition turbulence model at different angles of attack for flow Reynolds number of 5 · 10 5 . The aerodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Counter-rotating vortices were also observed by Poelma [19] in their study using a dynamically-scaled wing in mineral oil at Re of 256. In the numerical study at higher Reynolds numbers of 10 4 to 10 6 done by Wei et al, [20] vortex dipoles were also seen in the flow visualization.…”
Section: Introductionmentioning
confidence: 75%
“…Counter-rotating vortices were also observed by Poelma [19] in their study using a dynamically-scaled wing in mineral oil at Re of 256. In the numerical study at higher Reynolds numbers of 10 4 to 10 6 done by Wei et al, [20] vortex dipoles were also seen in the flow visualization.…”
Section: Introductionmentioning
confidence: 75%
“…The collective pitch of main rotor decreases to zero at the end of the transition process. As the CRW adopts symmetric aerofoils [7], [14], the main rotor produces no lift now, and the lift is completely provided by the canard wing and horizontal tail. The power of the main rotor can be cut off now and the main rotor will gradually speed down.…”
Section: A Transition Scheme Of the Crw Aircraftmentioning
confidence: 99%
“…He et al [5] and Deng et al [6] studied the aerodynamic interference between the main rotor and fixed wings based on wind tunnel tests. Sun et al [7], [8] explored the aerodynamic characteristics of the aerofoil of main rotor using computational fluid dynamics (CFD). Pandya and Aftosmis [9] investigated the aerodynamic load change of CRW via non-viscous numerical simulation during transition from helicopter to fixed-wing mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poelma et al [22] studied a dynamically-scaled wing moving in mineral oil and observed a pair of counter-rotating structures (Re = ). Wei, et al [23] numerically studied elliptical airfoils at Reynolds numbers ranging from 10 4 to 10 6 and they also captured vortex dipoles in the flow visualization. The current work extends these published works by implementing the kinematics of bumblebees on the elliptical airfoil.…”
Section: Introductionmentioning
confidence: 99%